Differences in creating product innovations versus process innovations across European industries. (26th September 2019) - Will, Matthias Georg; Mellor, Robert B.
The performance of 1, 200 representative firms in the Czech Republic, Germany, Hungary, Poland, Romania and the Slovak Republic was analysed, differentiating between product innovation and three different forms of process innovations. This data was joined to the quality of societal institutions of the relevant country. With respect to product innovations, institutional quality exhibits mediate effects through financing of R&D and the design of the organisational structure, with larger technical/R&D departments being found in firms in environments of high societal quality. However firms located in European countries with a relatively low institutional quality, develop predominantly more process innovations. Regarding industrial sector, the data reveals that firms in the wholesale and trade areas follow quite different innovation patterns compared to manufacturing/production. Manufacturing firms make predominantly product innovations, often financed by external sources, whereas firms in wholesale and trade make more process innovations and these tend to be financed by internal sources.